A PLIN1 polymorphism is associated with fat production in male emus - Yuichi Koshiishi; Ryo Takahashi; Michiko Murata-Okubo; Yuichi Kameyama; Kousaku Souma; Hiroki Hirayama; Kenta Wada (Poultry Science)
The emu (Dromaius novaehollandiae) is a novel poultry species that produces meat, eggs, and fat. Although emus have recently been domesticated, genetic improvements to establish strains have scarcely progressed. In this study, we investigated the relationship between production traits and perilipin 1-encoding gene (PLIN1) polymorphisms in the emus. We determined the partial complementary DNA (cDNA) sequence of the PLIN1, which is involved in lipid droplet formation. We identified four nucleotide substitution sites (c.270C>T, c.321T>C, c.587A>T, and c.639C>T) in the PLIN1 gene of emus. Of these, c.587A>T is a non-synonymous substitution that converts lysine to methionine at the 196th codon (p.K196M). Although p.K196M was predicted to affect the production traits of emus, a large deflection in genotype frequency was observed in this study; thus, we could not investigate the relationship between genotypes and phenotypes. In males, the fat yields of the CC, CT, and TT genotypes in c.270C>T were 0.25 ± 0.06, 0.22 ± 0.06, and 0.21 ± 0.07 kg, respectively, while the meat yields of the CC, CT, and TT genotypes in c.270C>T were 0.15 ± 0.01, 0.16 ± 0.02, and 0.16 ± 0.03 kg, respectively. These results indicate that male emus with the CC genotype had a significantly higher fat content and lower meat productivity than male emus with the other genotypes (P < 0.05). Therefore, c.270C>T in PLIN1 affects fat and meat production in males. Our findings may contribute to the effective genetic improvement of the emus.